Fostering successful and sustainable collaborations to advance implementation science: the adolescent HIV prevention and treatment implementation science alliance. (31st August 2020) - Sturke, Rachel; Vorkoper, Susan; Bekker, Linda‐Gail; Ameyan, Wole; Luo, Chewe; Allison, Susannah; Walker, Damilola; Kapogiannis, Bill; Guay, Laura
Abstract: Introduction: HIV continues to devastate the adolescent population in sub‐Saharan Africa (SSA). The complex array of interpersonal, social, structural and system‐level obstacles specific to adolescents have slowed progress in prevention and treatment of HIV in this population. The field of implementation science holds promise for addressing these challenges. Discussion: There is growing consensus that enhanced interactions between researchers and users of scientific evidence are important and necessary to tackle enduring barriers to implementation. In 2017, the Fogarty International Center launched the Adolescent HIV Prevention and Treatment Implementation Science Alliance (AHISA) to promote communication and catalyse collaboration among implementation scientists and implementers to enhance the cross‐fertilization of insights as research advances and the implementation environment evolves. This network has identified key implementation science questions for adolescent HIV, assessed how members' research is addressing them, and is currently conducting a concept mapping exercise to more systematically identify implementation research priorities. In addition, AHSA pinpointed common challenges to addressing these questions and discussed their collective capacity to conduct implementation science using the shared learning approach of the network. Specifically, AHISA addresses challenges related to capacity building, developing mentorship, engaging stakeholders, and involving adolescents through support for training efforts and funding region‐/country‐specific networks that respond to local issues and increase implementation science capacity across SSA. Conclusions: Innovative platforms, like AHISA, that foster collaborations between implementation science researchers, policymakers and community participants to prioritizes research needs and identify and address implementation challenges can speed the translation of effective HIV interventions to benefit adolescent health.